Development of Student Worksheets (LKPD) on Integer Topics to Improve Seventh-Grade Students’ Mathematical Problem Solving Abilities at SMP Negeri 3 Halongonan - Harahap, Nia Helmita; Lubis, Mara Samin (Universitas Wiralodra, 2026)
The development of appropriate learning materials is essential to support active learning and to enhance students’ understanding of mathematical concepts, particularly in problem-solving activities that require logical and systematic thinking. This study aimed to develop Student Worksheets (LKPD) on integer topics that meet the criteria of validity, practicality, and effectivity in improving seventh-grade Students’ Mathematical Problem-Solving Abilities at SMP Negeri 3 Halongonan. This research applied a Research and Development (R&D) method based on the 4D development model, which includes the stages of define, design, develop, and disseminate. The participants of this study were seventh-grade students at SMP Negeri 3 Halongonan. The instruments used in this study consisted of validation sheets assessed by media and subject-matter experts, student response questionnaires, and a test measuring mathematical problem-solving skills. The results indicated that the developed worksheets achieved a validity score of 87.27% from media experts, categorized as highly valid, and 75% from subject-matter experts, categorized as valid. The practicality test showed a percentage of 67.26%, indicating that the worksheets were practical and easy to implement in classroom learning activities. The effectiveness of the worksheets was indicated by an increase in students’ mathematical problem-solving skills, as reflected by an N-gain value of 0.55, classified as category. These findings suggest that the developed worksheets help students better understand integer concepts, increase learning engagement, and support the development of mathematical reasoning skills. Therefore, the developed LKPD is considered appropriate and practical to implement as a mathematics teaching medium for integer topics for seventh-grade students at SMP Negeri 3 Halongonan.